2022
DOI: 10.1002/asna.20220083
|View full text |Cite
|
Sign up to set email alerts
|

Strange stars confronting with the observations: Non‐Newtonian gravity effects, or the existence of a dark‐matter core

Abstract: We find that the existence of strange stars is ruled out by the dimensionless tidal deformability of a 1.4 M ⊙ star of GW170817 and the mass of PSR J0740 + 6620, both for the standard MIT bag model and for the density-dependent quark mass model. However, if non-Newtonian gravity effects are considered, strange stars can exist for certain ranges of the values of the non-Newtonian gravity parameter. An alternative explanation to these observations is to suppose that strange stars in GW170817 have a dark-matter c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…The parameters of the SQM model could be constrained by the observations of compact stars [53][54][55][56][57][58][59][60][61][62][63]. For the MIT bag model, Weissenborn et al [53] found that the parameters of the model could be constrained if one demands that the maximum mass of SSs must be greater than the mass of PSR J1614-2230 (1.97 ± 0.04 M [64]).…”
mentioning
confidence: 99%
“…The parameters of the SQM model could be constrained by the observations of compact stars [53][54][55][56][57][58][59][60][61][62][63]. For the MIT bag model, Weissenborn et al [53] found that the parameters of the model could be constrained if one demands that the maximum mass of SSs must be greater than the mass of PSR J1614-2230 (1.97 ± 0.04 M [64]).…”
mentioning
confidence: 99%